Suicidal thoughts and behaviour among South African adolescents living with HIV: Can social support buffer the impact of stigma? - Casale, M.; Boyes, Mark; Pantelic, M.; Toska, E.; Cluver, L. (Elsevier BV, 2019)
Background: Adolescents living with HIV represent a high-risk population for suicidal ideation and attempts, especially in low-income settings. Yet little is known about risk and protective factors for suicide in this population. Methods: A moderated mediation model was employed to test for potential (a) effects of stigma on suicidal ideation and attempts, both direct and mediated through depression and (b) direct and stress-buffering effects of social support resources on depression and suicidal ideation and attempts, among 1053 HIV-positive 10–19-year-old adolescents from a resource-scarce health district in South Africa. The survey data was collected using full community sampling of 53 clinics and tracing to over 180 communities. Effects of two support resources were tested: perceived support availability from the adolescents’ social network and structured clinic support groups. Stigma was measured using the ALHIV-SS scale, depression through the CDI short form and social support through items from the MOS-SS. Results: Stigma was a risk factor for depression (B = 0.295; p < 001) and for suicidal thoughts and behaviour (B = 0.185; p <.001). Only perceived support availability was directly associated with less depression (B = -0.182, p <.001). However, both perceived support availability and support group participation contributed to the overall stress-buffering effects moderating the direct and indirect relationships between stigma and suicidal thoughts and behaviour. Limitations: The data used in this study was self-reported and cross-sectional. Conclusions: Findings suggest that strengthening multiple social support resources for HIV-positive adolescents, through early clinic and community-based interventions, may protect them from experiencing poor mental health and suicidal tendencies.